Optimalisasi Proses Pembelajaran di SD Melalui Penelitian Tindakan Kelas - Maria Rinta Putri Wardhani (Universitas Nusantara PGRI Kediri, 2024)
Classroom action research is a form of self-reflection for a teacher to be able to understand social situations including in education which aims to improve the practice carried out by the teacher himself so that practice can run as expected and is relevant to the situation. Purpose Carrying out community service activities by conducting classroom action research (CAR) activities is an effort to improve the quality of learning which is one of the competency demands. In its implementation, it uses theoretical material presentation methods, discussions, and exercises for making research proposals. The implementation technique is the preparation of proposals which includes clinical proposal preparation, conveying several learning models that will be used in research, research implementation assistance, and preparation of the final report. The results achieved in this activity, the participants increased their understanding of PTK so that the knowledge obtained by the participants could be used as a process of improving learning in class. By increasing this ability the learning process can run optimally.